2018
DOI: 10.7710/2162-3309.2246
|View full text |Cite
|
Sign up to set email alerts
|

Marketing via Email Solicitation by Predatory (and Legitimate) Journals: An Evaluation of Quality, Frequency and Relevance

Abstract: This article underwent fully-anonymous peer review in accordance with JLSC's peer review policy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…As such, the commitment by big publishers including The Lancet and Cell Press in 2020 to share research data and findings relevant to the novel coronavirus has demonstrated the value of open access (Tavernier, 2020). However, researchers need to be careful in their quest to use and publish in open access platforms as there is a growing influx of predatory journals with qestionable practices and dubious quality (Ayeni & Adetoro, 2017;Burggren, Madasu, Hawkins, & Halbert, 2018;Frederick, 2020;Zhao, 2014). Researchers have to constantly sieve disinformation and misinformation in research results relating to the COVID-19 pandemic (Baines & Elliott, 2020), which are usually spread through platforms that are open and easily accessible to the public.…”
Section: Discussionmentioning
confidence: 99%
“…As such, the commitment by big publishers including The Lancet and Cell Press in 2020 to share research data and findings relevant to the novel coronavirus has demonstrated the value of open access (Tavernier, 2020). However, researchers need to be careful in their quest to use and publish in open access platforms as there is a growing influx of predatory journals with qestionable practices and dubious quality (Ayeni & Adetoro, 2017;Burggren, Madasu, Hawkins, & Halbert, 2018;Frederick, 2020;Zhao, 2014). Researchers have to constantly sieve disinformation and misinformation in research results relating to the COVID-19 pandemic (Baines & Elliott, 2020), which are usually spread through platforms that are open and easily accessible to the public.…”
Section: Discussionmentioning
confidence: 99%
“…In the above-described context, the preparation of authors, especially those who are in the early stages of their career as researchers, is critical. Senior faculty members play a key role in advising their younger and unexperienced colleagues on the publishing process (Burggren et al, 2018;Liyanapathirana, 2019;Watson, 2019). Furthermore, contrary to what could be expected, it may happen that many university students, even at the graduate level, are not very familiar or particularly concerned with these quality issues of scientific publication (Liyanapathirana, 2019;Santos & Serpa, 2017).…”
Section: Preparation Of the Authorsmentioning
confidence: 99%
“…Given that the assessment of scientific production in the country defines the allocation of financial resources, these assessment criteria are widely used by researchers in the search for better scores and, hence, higher funding. Burggren et al (2018) advocate that, instead of using complex metrics, evaluation committees, whether for merit, promotion or tenure, should base their assessments on the quality of the work published, as well as the quality of the journal itself. This would lead to a redefinition in terms of the choice of the journals to publish in on the part of academics (Shaghaei et al, 2018;Teixeira da Silva & Tsigaris, 2018;Cress & Sarwer, 2019;Severin & Low, 2019).…”
Section: Institutional Preventionmentioning
confidence: 99%